Effects of pelvic floor bioelectrical stimulation on frozen embryo transfer patients with thin endometrium. (January 2019) - Yuan, Bing; Zheng, Hong; Xu, Minling; Mu, Xiaoli; Huang, Fengcai
This study was to observe the effects of pelvic floor bioelectrical stimulation on pregnancy outcome and serum estradiol (E2) and progesterone (P) levels in frozen embryo transfer patients with thin endometrium. 120 cases frozen embryo transfer patients with thin endometrium in our hospital from March 2016 to April 2017 were selected. These patients received artificial cycle replacement plan before embryo transfer. According to whether pelvic floor bioelectrical stimulation therapy was accepted, 120 cases of thin endometrial frozen embryo transfer were divided into control group and observation group. 50 cases of the control group received artificial cycle to prepare for embryo transplantation, while 70 cases of observation group received bioelectrical stimulation as intervention treatment on the basis of artificial cycle. The intima thickness, subintimal hemodynamic parameters, embryo implantation rate, and clinical pregnancy rate were compared between the two groups before and after treatment. There was no significant difference in endometrial thickness between the two groups on the 10th day of menstruation ( P  > 0.05). The thickness of endometrium and the index of intima growth in the observation group were significantly higher than those in the control group ( P  < 0.05). The pulsatility index, resistance index, and systolic and diastolic blood flow velocity ratio of subintimal blood flow in the observation group were significantly higher than those in the control group ( P  < 0.05). Before treatment, there was no significant difference in serum E2 and P between the two groups ( P  > 0.05). After treatment, the improvement of serum E2 and P in the observation group was significantly better than that of the control group ( P  < 0.05). The embryo implantation rate (25.7%) in the observation group was significantly higher than that in the control group (17.0%) ( P  < 0.05). The clinical pregnancy rate (47.1%) in the observation group was significantly higher than that in the control group (30%) ( P  < 0.05). In conclusion, the intervention of pelvic floor bioelectrical stimulation can improve the blood perfusion of thin endometrium, improve the endometrial receptivity, increase the implantation rate of frozen embryo transfer in patients with thin endometrium, and improve the level of serum estradiol and progesterone.